The role of cross-border power transmission in a renewable-rich power system – A model analysis for Northwestern Europe. (1st May 2020) - Chen, Yi-Kuang; Koduvere, Hardi; Gunkel, Philipp A.; Kirkerud, Jon Gustav; Skytte, Klaus; Ravn, Hans; Bolkesjø, Torjus F.
Abstract: This study quantifies the economic potential of cross-border transmission to a decarbonized future Northwestern European power system through the energy model Balmorel. A scenario with modelled optimal transmission capacity at lowest total system costs is compared to the scenario with given capacity level of existing and planned projects. Increased transmission investments decrease total system costs and regional price difference. It benefits particularly wind power deployment and thus, lowers CO2 emissions in the power and heat sector. The impacts are, nevertheless, distributed asymmetrically to northern and western stakeholders. Northern consumers receive higher power prices, but the revenues of wind and hydropower producers also increases. Meanwhile, western consumers receive lower power prices, but gas power producer revenues decrease. Highlights: Benefits and impacts of increased Northwestern European cross-border transmissions are analytically accessed. Increased cross-border transmissions reduce overall system costs and CO2 emissions. Northern clean energy producers benefit while western gas power producers are impacted. Northern consumer costs increase while western consumers receive lower prices.